Molecular pathogenesis of pediatric thyroid carcinoma. (5th May 2021) - Mitsutake, Norisato; Saenko, Vladimir
ABSTRACT: There has been little understanding of the molecular pathogenesis of pediatric thyroid cancers. Most of them are histologically classified as papillary thyroid carcinoma (PTC). Ionizing radiation is the most important environmental factor to induce PTC, especially in children. Particularly, radiation-related pediatric PTCs after the Chernobyl accident provided invaluable information. In addition, the recent accumulation of sporadic pediatric PTC cases, partly due to advances in diagnostic imaging, has also provided insight into their general pathogenesis. In PTC development, basically two types of genetic alterations, fusion oncogenes, mainly RET/PTC, and a point mutation, mainly BRAF V600E, are thought to play a key role as driver oncogenes. Their frequencies vary depending on patient age. The younger the age, the more prevalent the fusion oncogenes are. Higher incidence of fusion oncogenes was also observed in cases exposed to radiation. In short, fusion oncogenes are associated with both age and radiation and are not evidence of radiation exposure. The type of driver oncogene is shifted toward BRAF V600E during adolescence in sporadic PTCs. However, until about this age, fusion oncogenes seem to still confer dominant growth advantages, which may lead to the higher discovery rate of the fusion oncogenes. It has been postulated that RET/PTC in radiation-induced PTC is generated by ionizing radiation; however, there is an interesting hypothesis that thyroid follicular cell clones with pre-existing RET/PTC were already present, and radiation may play a role as a promoter/progressor but not initiator. Telomerase reverse transcriptase gene ( TERT ) promoter mutations, which are the strongest marker of tumor aggressiveness in adult PTC cases, have not been detected in pediatric cases; however, TERT expression without the mutations may play a role in tumor aggressiveness. In this paper, the recent information regarding molecular findings in sporadic and radiation-associated pediatric PTCs is summarized.